Pengelolaan Aset Berbasis Wealth Management Dalam Upaya Meningkatkan Nilai Ekonomi Pondok Pesantren Darul Ulum Banyuanyar Pamekasan - Yakin, Ainol; Shalehoddin, Shalehoddin (Al-Amien Prenduan for Islamic Institute, 2023)
The economic independence of Islamic boarding schools has become a necessity, in fact there is a lot of foreign investment that has entered and controlled the Indonesian market, while the community collectivity has become more of a consumer, this is very worrying, such as the presence of Alfa Mart and Indomart, large capital owners in rural corners. evidence of the increasing powerlessness of local collective economic power. The aim of this research is to find out how the governance carried out at the Darul Ulum Banyuanyar Pamekasan Islamic boarding school is based on management skills, and also the efforts made to increase the economic value of the Islamic boarding school. This research uses a qualitative approach, and attempts to find and describe narratively the activities carried out. The results of this research: Broadly speaking, there are two types of eset management at the Darul Ulum Banyuanyar Islamic Boarding School; The first is that the assets are managed within the Islamic boarding school, and the second is that the assets are managed outside the Islamic boarding school where the assets belong to the alumni. There are also three business terms: first, the wealth and assets managed by the Islamic boarding school are assets owned by the Islamic boarding school family which are fully handed over to the general treasurer to manage. the second is a business or business unit managed by an Islamic boarding school whose capital comes from the Islamic boarding school. Third, the form of business managed by Islamic boarding school alumni outside the boarding school.